1H spin–lattice relaxation in water solution of 209Bi counterparts of Gd3+contrast agents. (18th April 2019) - Kruk, Danuta; Umut, Evrim; Masiewicz, Elzbieta; Hermann, Petr; Scharfetter, Hermann
ABSTRACT: 1 H spin–lattice relaxation studies of water solutions of Bismuth-ethylenediamine-tetraacetic acid (Bi-EDTA), Bismuth-ethylenediamine-tetrakis(methylenephosphonic) acid (Bi-EDTP), Bismuth-1, 4, 7, 10-tetraazacyclododecane-1, 4, 7, 10-tetraacetic acid (Bi-DOTA), Bismuth-1, 4, 7, 10-tetraazacyclododecane-1, 4, 7, 10-tetrakis(methylenephosphonic acid) (Bi-DOTP) and Bismuth-1, 4, 7, 10-tetraazacyclododecane-1, 4, 7-triacetic acid (Bi-DO3A) have been performed in order to compare Quadrupole Relaxation Enhancement (QRE) effects with Paramagnetic Relaxation Enhancement (PRE) from the perspective of exploiting the first one as a novel contrast mechanism for Magnetic Resonance Imaging (MRI). The selected compounds can be considered as 209 Bi counterparts of Gd 3+ complexes. The relaxation experiments have been performed in a broad frequency range of 5 kHz–30 MHz. The relaxation contribution associated with QRE has been extracted from the data and compared with PRE. Similarities and differences between the two effects have been discussed. GRAPHICAL ABSTRACT: